2022
DOI: 10.1002/alr.23051
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic surgery is superior to intensity‐modulated radiotherapy in the treatment of advanced recurrent nasopharyngeal carcinoma

Abstract: Background:The choice between endoscopic surgery and re-radiotherapy as the main treatment modality in patients with advanced recurrent nasopharyngeal carcinoma (rNPC) remains controversial. Therefore, in this study, we compared the efficacies of endoscopic surgery and intensity-modulated radiotherapy (IMRT) in patients with rNPC. Methods: All patients with advanced rNPC (T3 and T4) who underwent salvage treatment were enrolled from January 2009 to December 2020. Overall survival (OS) was analyzed using a log-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…The most common treatment for rNPC is salvage surgery and IMRT. Evidence is accumulating that endoscopic surgery is superior to IMRT in the treatment of rNPC [ 9 , 20 ]. Hua et al reported that the 3-year overall survival (OS) in surgery groups of rT3 and rT4 tumours was 68.8 and 36.9%, respectively, which was longer than that of patients receiving IMRT [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most common treatment for rNPC is salvage surgery and IMRT. Evidence is accumulating that endoscopic surgery is superior to IMRT in the treatment of rNPC [ 9 , 20 ]. Hua et al reported that the 3-year overall survival (OS) in surgery groups of rT3 and rT4 tumours was 68.8 and 36.9%, respectively, which was longer than that of patients receiving IMRT [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that recurrences amenable to surgery with favourable outcomes and a high likelihood of negative margins include the majority of rT1 and early rT2 disease and selected rT3 disease with a small disease volume and minimal skull base involvement [ 21 23 ]. With the development of arterial embolization techniques and the accumulation of surgeons’ anatomical experience related to the nasopharyx and skull base, indications are expanding to include rT3 and rT4 disease [ 9 , 24 26 ]. Wong et al [ 25 ] reported favourable patient outcomes with advanced rNPC (rT3 and rT4) who underwent an endoscopic approach, and the two-year OS (66.7%) and DFS (40.0%) results basically agreed with the our previous data (OS: 67.1%; DFS: 37.3%) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exclusion criteria were as follows: (1) patients with ICA embolization or external carotid‐intracranial artery bypass grafting before surgery; (2) patients with retropharyngeal and/or cervical lymph node metastasis; (3) patients with distant organ metastasis; and (4) a lack of important clinical variable data and follow‐up data. In addition, extensive invasion of intracranial structures, especially important blood vessels and nerves, or invasion of intracranial structures after previous radiotherapy with obvious radiation‐induced brain edema are also considered as contraindications of endoscopic surgery 9,23 …”
Section: Methodsmentioning
confidence: 99%
“…In addition, extensive invasion of intracranial structures, especially important blood vessels and nerves, or invasion of intracranial structures after previous radiotherapy with obvious radiation-induced brain edema are also considered as contraindications of endoscopic surgery. 9,23 We collected the demographic characteristics, pathological classification, AJCC/UICC rT staging, closest distance between the tumor margin and ICA on enhanced MRI (distance ≥ 5 mm, 1.8 mm < distance < 5 mm, and distance ≤ 1.8 mm), invasion of the dura mater, overall survival time, and survival time without tumor progression. The criteria for dural invasion were based on the criteria set in the study of McIntyre et al, as "the presence of ≥2 mm of dural thickening, loss of hypointense zone, and nodular dural enhancement."…”
Section: Patient Selectionmentioning
confidence: 99%